2003
DOI: 10.1136/bjo.87.11.1324
|View full text |Cite
|
Sign up to set email alerts
|

Female reproductive factors and open angle glaucoma: the Blue Mountains Eye Study

Abstract: Aims: To determine whether endogenous oestrogen exposures are associated with open angle glaucoma (OAG). Methods: The Blue Mountains Eye Study examined 2072 women aged 49-97 years during 1992-4. Questions about female reproductive factors included age at menarche and menopause, parity, and use of hormone replacement therapy. Applanation tonometry, visual field tests, and stereo-optic disc photographs were performed. OAG was diagnosed when glaucomatous visual fields matched optic disc changes. Ocular hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 34 publications
(26 reference statements)
5
83
2
1
Order By: Relevance
“…These findings are consistent with the 2 other studies that examined this relation: for current PMH users versus never users the odds ratios were 0.54 (0.17 to 1.74) in the Rotterdam Study 21 and 0.8 (0.3 to 2.2) in the Blue Mountain Eye Study. 22 Biologically, it is well known that estrogen up-regulates endothelial nitric oxide synthase (eNOS) activity, an enzyme that produces the vasodilator nitric oxide. 39 Therefore, declining estrogen levels in women could lead to reduced nitric oxide production which could contribute to an unfavorable optic nerve vascular hemodynamic profile, variable IOP (eNOS is expressed in the trabecular meshwork 40 ), and subsequent loss of retinal ganglion cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with the 2 other studies that examined this relation: for current PMH users versus never users the odds ratios were 0.54 (0.17 to 1.74) in the Rotterdam Study 21 and 0.8 (0.3 to 2.2) in the Blue Mountain Eye Study. 22 Biologically, it is well known that estrogen up-regulates endothelial nitric oxide synthase (eNOS) activity, an enzyme that produces the vasodilator nitric oxide. 39 Therefore, declining estrogen levels in women could lead to reduced nitric oxide production which could contribute to an unfavorable optic nerve vascular hemodynamic profile, variable IOP (eNOS is expressed in the trabecular meshwork 40 ), and subsequent loss of retinal ganglion cells.…”
Section: Discussionmentioning
confidence: 99%
“…20 One population-based, cross-sectional study where the mean age of participants was 68.1 years observed that entering menopause before age 45 was associated with a 2.6-fold increased risk of open-angle glaucoma, compared with entering menopause at age 50 or older. 21 The Blue Mountain Eye Study where the mean age of women enrolled was 66.4 years found a nonsignificant positive association between early menopause and open-angle glaucoma, 22 whereas the Aravind Comprehensive Eye Survey which evaluated a fairly young population (mean age 50.1 y) reported that female reproductive factors were unrelated to POAG. 23 To our knowledge, there is no prospective study of the relation between the attributes of female reproductive aging and POAG.…”
mentioning
confidence: 98%
“…Lee et al [11] showed that HRT reduces but not statistically significant intraocular pressure in open angle glaucoma.…”
Section: Glaucomamentioning
confidence: 98%
“…In addition, when estrogen bind to their receptor in retina, nitric oxide is produced; this dilates the vessels and helps the outflow of aqueous humor from the trabecular meshwork. These today are considered as the possible mechanisms by which estrogen protect against glaucoma [11].…”
Section: Glaucomamentioning
confidence: 99%
See 1 more Smart Citation